None of them are correct.
The solution to the quadratic equation 2x² - 4x - 3 = 0 is x = 1 ± √2.5
<h3>What is an
equation?</h3>
An equation is an expression that shows the relationship between two or more numbers and variables.
Solving the polynomial using completing the square:
2x² - 4x - 3 = 0
First divide through by 2:
x² - 2x - 3/2 = 0
add 3/2 to both sides:
x² - 2x - 3/2 + 3/2 = 0 + 3/2
x² - 2x = 3/2
add the square of half the coefficient x to both sides:
x² - 2x + 1 = 3/2 + 1
(x - 1)² = 2.5
taking square root:
x - 1 = ±√2.5
x = 1 ± √2.5
The solution to the quadratic equation 2x² - 4x - 3 = 0 is x = 1 ± √2.5
Find out more on equation at: brainly.com/question/2972832
#SPJ1
Answer:
what do u want me to do
Step-by-step explanation:
Area = side * side
Area of the square = 6 1/9 * 6/1/9
= 36 1/81
Answer:
f•g(x) = f(x)•g(x)
f•g(x) = (2x-1) (x²-2x+1)
= 2x³-4x²+2x-x²+2x-1
= 2x³-5x²+4x-1